Brainhacker : master memory, focus, emotions, and more to unleash the genius within - Farrow, David, 1975- (Ascent Audio, 2023)
If you feel like your brain is "glitching," or working against you, know that you're not stuck with the brain biology gave you. An upgrade is possible. In Brainhacker, you'll learn how to "rewire" your brain and boost its power. David Farrow, author of The Farrow Method, helps you get inside your own head and call the shots, with concrete exercises and tips to train your brain to work for you. These tricks can instantly boost your memory, improve your reading speed, help you push away pain, and form life-changing habits that actually last-with techniques as simple as a hand movement or a little bit of imagination. On average, we waste forty days of the year compensating for our bad memory. Many of us suffer from insomnia, stress, and chronic pain. The COVID-19 pandemic has caused a huge surge in the already-huge number of people suffering from burnout and mental health problems. But all of this, from memory to ADHD symptoms to sleep problems, can be transformed with the simple hacks you'll find in this book. If you're ready to tap into the full power of your brain, Brainhacker is your all-in-one guide to hacking into your brain-and making it as powerful as it can be